Mean Platelet Volume As Retinopathy Diabetic Predictive Factor in Peripheral Hospital: Could it be? Oral Presentation - Observational Study - General practitioner - Masniah; Maulana, Denny Indra (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesSeveral studies conducted that diabetic retinopathy (DR) pathogenesis may be linked tomicrocirculation disorders and microvascular damage. Platelets have a significant role inmicrocirculation changes that lead to microvascular injury. Mean Platelet Volume (MPV) is used as amarker to indicate the platelet’s average size and activity. The association between MPV and DR in apatient’s blood sample has been established. Aim of this study is to evaluate the association of MPVwith DR in our population. MethodsThis was a cross-sectional study in Brigjend H. Hasan Hospital within 183 patients which classifiedinto three groups including: I. DM without DR (n=61), II. DM with Non-proliferative DR (n=61), andIII. DM with proliferative DR (n=61). Data about gender, age and laboratory markers (MVP, HbA1C,fasting blood glucose) were collected, then analyzed using SPSS. ResultsMPV value was significantly higher in group II and III compared to group I (p<0.001). The MPVvalue was also significantly higher in PDR Group compared to NPDR Group (adj. OR 7.91, 95% CI:3.79-16.5). The FBG value also significantly higher in group II and III compared to group I(p=0.012). On the other hand, HbA1C value mean was higher in group II and III but not statisticallysignificant (p=0.052). ConclusionThis study demonstrated relationship between higher MPV with DR and its severity. Consideringthat MPV can be easily measured and suitable as parameter reflective platelet function, DR and itsprogressivity can be clinically monitored using this method.